PENGARUH ASUPAN VITAMIN D TERHADAP TEKANAN DARAH SISTOLIK TIKUS PUTIH (Rattus norvegicus) JANTAN. - Endang Wahyuni; Setiaji Dermawan (Holistik Jurnal Kesehatan, 2019)
ABSTRACT: RELATIONSHIP OF ZINC AND VITAMIN A INTAKE WITH DIARRHEA INCIDENCE IN CHILDREN 1-5 YEARS Background: Diarrhea is a serious health problem in developing countries. Diarrhea is a major cause of morbidity and mortality in children 1-5 years. Infectious diarrhea is the biggest cause of diarrhea, that can be caused by viruses, bacteria, and parasites. Diarrhea can be prevented by giving children nutritious food so they have a strong immunity. Some nutrition that can prevent diarrhea are zinc and vitamin A. This study want to determine the relationship between zinc and vitamin A intake with the diarrhea incidence Methods: This was an analytic with cohort design using zinc and vitamin A intake as an independent variables and diarrhea incidence as dependent variabel. Sample was 54 children under 5 years, at Yosomulyo Health Center, Metro in 2015. Yosomulyo Health Center was selected using purposive sampling technique, because it had the most diarrhea incidence in Metro City. Results: Subject with low zinc intake were 7 respondens (13%), 3.7% respondens with low vitamin A intake, and 9.3% of subject had a diarrhea. As a conclusion, there is a relationship between zinc and vitamin A intake with diarrhea incidence in children 1-5 years (P<0,05). To improve zinc and vitamin A intake in children 1-5 years, it was suggested that nutrition officer of Health Center must be proactive in giving counseling to the mother and give an effort to vitamin A distribution so all children under 1-5 years have it in February and AugustPendahuluan: Penyakit diare merupakan masalah kesehatan yang serius di negara-negara berkembang. Diare adalah penyebab utama morbiditas dan mortalitas pada balita kurang dari 5 tahun, Diare infeksiosa merupakan penyebab kejadian terbesar diare, yang dapat disebabkan oleh virus, bakteri, dan parasit. Diare dapat dicegah dengan memberikan anak makanan bergizi sehingga anak mempunyai kekebalan yang kuat. Zat gizi yang dapat mencegah terjadinya diare diantaranya adalah seng dan vitamin A. Tujuan penelitian adalah untuk mengetahui hubungan asupan seng dan vitamin A dengan kejadian diare.Metode: Penelitian ini menggunakan desain studi kohort, dengan variable independen adalah asupan seng dan vitamin A dan variabel dependen adalah kejadian diare. Sampel berjumlah 54 anak, di Puskesmas Yosomulyo Kota Metro tahun 2015, yang dipilih secara purposive sampling karena mempunyai kejadian diare terbesar di wilayah MetroHasil: Hasil penelitian menunjukkan bahwa responden dengan asupan seng kurang sebanyak 7 responden (13%), Sebanyak 3.7% responden mempunyai asupan vitamin A kurang, dan Sebanyak 9.3% responden mengalami diare. Ada hubungan antara asupan seng dan vitamin A dengan kejadian diare pada anak umur 1-5 tahun (p<0,05). Untuk meningkatkan asupan seng dan vitamin A pada anak balita, diperlukan keaktifan petugas gizi Puskesmas dalam memberikan penyuluhan kepada ibu balita dan mengusahakan agar semua anak di bawah 5 tahun mendapatkan kapsul vitamin A di bulan February dan Agustus